MRI study of white matter microstructural alterations in attention deficit/hyperactivity disorder - Bu Xuan; Huang Xiaoqi (Sichuan jingshen weisheng, 2021)
The development of cerebral white matter is essential for the establishment of normal behavior and cognitive functions， and several studies have shown that the alterations in white matter microstructure are associated with core symptoms and cognitive deficits in attention deficit/hyperactivity disorder （ADHD）， suggesting that the abnormalities in cerebral white matter may be one of the neurological underpinnings of the disease. This article aims to review and summarize the magnetic resonance imaging studies of the white matter microstructure in children and adolescents with ADHD， to summarize the characteristics of the alterations in the white matter fiber tracts of ADHD， and to analyze the relationships with the clinical manifestations of the disease. Thereafter， the potential pathogenesis of ADHD is explored， thus providing a guidance for the future studies.